Charles Taylor, Sources of the self. The making of the modern identity, Cambridge, Harvard University Press, 1989, 601 páginas. - Rossi, Luis Alejandro (Universidad Nacional de Quilmes, 1995)
Fil: Rossi, Luis Alejandro. Universidad Nacional de Quilmes; Argentina.